Germination of yellow passionfruit seeds in aqueous extract of purple nutsedge and gibberellic acid - Villa, Fabíola; França, Daiane Luckmann Balbinotti; Rech, Angela Laufer; Moura, Claudia Andrade; Fuchs, Felipe (Revista de Ciências Agroveterinárias, 2016)
Allelopathy refers to the ability of certain plant has to interfere with the metabolism of other compounds by chemicals released into the environment. Cyperus rotundus is a typical example of such a plant, having a high IBA concentration and being able to influence and act on germination and rooting of the other plants. The aim of this study was to evaluate the effect of bulbs and leaves extracts of Cyperus rotundus and gibberellic acid on the yellow passion fruit germination cycle. To obtain the aqueous extract bulbs and leaves were used along with a concentration of 1 g 10 mL-1 (p/v) (1 g of material plant to 10 mL of distilled water), forming stock solutions. Extracts were diluted in five concentrations (20, 40, 60, 80 and 100%) and five concentrations of gibberellic acid (200, 400, 600, 800 and 1000 mg L-1 GA3) were used. As a control treatment we used distilled water. The experimental design was completely randomized, with 16 treatments, five replicates, totaling 80 sampling units, each unit containing ten seeds. Daily counts were performed on the number of germinated seeds for subsequent calculation of germination percentage and germination speed index. Seeds of yellow passion fruit treated with concentrations of gibberellic acid had their germination inhibited and it is not recommended in the germination of the species. Concentrations of aqueous extract of leaves and sedge did not affect the germination of yellow passion fruit.